Scientific and Practical Aspects of Bitumen Emulsion Mastic Creation - F. Kemalov, Alim; A. Kemalov, Ruslan; Serge-Bertrand, Adiko; Alpa Oumar, Diakite (International Journal of Engineering and Technology, 2018)
It is interesting to consider the possible application as an alternative raw material in the manufacture of bituminous emulsion material residual bitumen grade BNN 80/120, production technology which implies a significant reduction in the proportion of paraffinic hydrocarbons by allocating them in the oil fractions in the evacuation of heavy petroleum residues. As a raw material in the production of BEM they should use the bitumen obtained from the heavy oils of naphthenic aromatic base with a minimum content (up to 2% by weight) [1] of high-molecular straight-chain paraffinic hydrocarbons (P-HC), whose reserves are largely limited and difficult to access. In this regard, the expansion of the raw material base of bitumen production due to the involvement of HOR resinous paraffin base confirms the relevance of the studies. The difficulties in the production of insulating BEMs, that meet the requirements of GOST 30693-2000 on the basis of oxidized HOR paraffin base, are explained by the fact that protective coatings (PK) from such materials with the decrease in the glass transition temperature (point) are characterized by an increased intensity of internal stress (Î´v) in the volume of BEM, in which the increase of the strength growth intensity (Î´p) occurs, so premature spontaneous destruction occurs in the process of oxidative destruction, i.e. in the conditions of their operation. This is explained by the fact that at the temperatures above Tst, highly elastic and plastic deformations develop in bitumen, and internal stresses relax easily. With decreasing Tst, the rigidity of bitumen increases sharply, the relaxation processes decelerate, and internal stresses increase substantially.Â Â